Contabilidade: ciência, técnica ou arte? - Tesche, Carlos Henrique; Vendruscolo, Carlos Otávio; Alves, Clodiana Brescovit; Wayerbacher, Leonardo; Schwez, Nicolau; Dalbén, Odilon José Bussata (Contabilidade Vista & Revista, 2009)
O artigo não tem resumo.